The Effect Of Discipline, Motivation And Satisfaction On Employee Performance In Hotels - Andi Wijaya; Agustin HP (ABM: International Journal of Administration, Business and Management, 2019)
One concept to maintain corporate image is employee performance. A concept that seeks to create a good and reliable Human Resources within the company to achieve the goals of the company itself. When the company has committed to maintain employee performance improvement will encourage companies to pay attention to the level of work discipline experienced by employees and the provision of proper work motivation to see the level of job satisfaction of each employee will make employees feel more eager in completing the work. The population of this study were non-permanent employees of Hotel ASTON Jember and the sample was set by 50 respondents. The variables analyzed in this research are work discipline, work motivation and job satisfaction as independent variable, and employee performance as dependent variable. The sampling method used is simple random Sampling in which all permanent employees have the opportunity to be sampled in this study. This type of research is an explanatory research.Research is a study that tries to explain a subject matter and there is a hypothesis testing and perform analysis of data obtained. Methods of data analysis using Multiple Linear Regression Analysis.The results of this study indicate that discipline, motivation and satisfaction simultaneously have a positive and significant effect on employee performance at Hotel ASTON Jember, partially work discipline has a positive and significant impact on employee performance at Hotel ASTON Jember, partially motivation of work has a positive and significant impact on performance Employees at Hotel ASTON Jember and job satisfaction have a negative and insignificant effect on the performance of Hotel ASTON Jember's employees. Keywords: Discipline, Motivation, Satisfaction, Performance